Inhaled Dry Powder of Antiviral Agents: A Promising Approach to Treating Respiratory Viral Pathogens - Tushar Saha; Zia Uddin Masum; Anik Biswas; Moushumi Afroza Mou; Sohag Ahmed; Tamal Saha (Viruses)
Inhaled dry powder formulations of antiviral agents represent a novel and potentially transformative approach to managing respiratory viral infections. Traditional antiviral therapies in the form of tablets or capsules often face limitations in terms of therapeutic activity, systemic side effects, and delayed onset of action. Dry powder inhalers (DPIs) provide a targeted delivery system, ensuring the direct administration of antivirals to the infection site, the respiratory tract, which potentially enhance therapeutic efficacy and minimize systemic exposure. This review explores the current state of inhaled dry powder antiviral agents, their advantages over traditional routes, and specific formulations under development. We discuss the benefits of targeted delivery, such as improved drug deposition in the lungs and reduced side effects, alongside considerations related to the formulation preparation. In addition, we summarize the developed (published and marketed) inhaled dry powders of antiviral agents.